2020
DOI: 10.1002/rcs.2179
|View full text |Cite
|
Sign up to set email alerts
|

End‐user evaluation of software‐generated intervention planning environment for transrectal magnetic resonance‐guided prostate biopsies

Abstract: Background This study presents user evaluation studies to assess the effect of information rendered by an interventional planning software on the operator's ability to plan transrectal magnetic resonance (MR)‐guided prostate biopsies using actuated robotic manipulators. Methods An intervention planning software was developed based on the clinical workflow followed for MR‐guided transrectal prostate biopsies. The software was designed to interface with a generic virtual manipulator and simulate an intervention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Lastly, before first-in-human studies, multisite animal studies will be required to assess the working of the proposed system in a minimally invasive setting (manual and robotic). It would further assist in understanding the functioning of the tele-mentoring system in an operating room environment, especially related to ergonomics of the hardware components used at the operative field (such as tracking frames for trocars and line-of-sight of the optical tracking system) and interaction with the software graphical user interfaces [ 45 – 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, before first-in-human studies, multisite animal studies will be required to assess the working of the proposed system in a minimally invasive setting (manual and robotic). It would further assist in understanding the functioning of the tele-mentoring system in an operating room environment, especially related to ergonomics of the hardware components used at the operative field (such as tracking frames for trocars and line-of-sight of the optical tracking system) and interaction with the software graphical user interfaces [ 45 – 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…hardware components used at the operative field (such as tracking frames for trocars and line-of-sight of the optical tracking system) and interaction with the software graphical user interfaces [45][46][47].…”
Section: Supplementary Informationmentioning
confidence: 99%
“…33,34 For interfacing with mixed reality environment, user studies have shown that hand gestures may not be a suitable mode for sending instructions and a suitable user-interface is required. 35,36…”
Section: Discussionmentioning
confidence: 99%
“…AR, augmented reality A goal in these studies was to investigate the use of an AR device, that is, the HoloLens, as an output interface for visualisation of biopsy planning. Although visualisation of the 3D interventional environment on a 2D screen is enough to plan a biopsy, 42 the additional visual properties of holograms have the potential to make biopsy planning easier to learn and execute. This is because visualisation through holographic AR provides true 3D visualisation, giving depth to the renderings.…”
Section: F I G U R Ementioning
confidence: 99%
“…The deformation caused by probe actuation can be addressed by acquiring a new set of real-time MR images to confirm the pose of the probe with respect to prostate and refreshing the visual information on the HMD before inserting the biopsy needle. 42 It should be noted that insertion of biopsy needle, in either Mode-I or Mode-II, also causes tissue deformation. Though the detection rate is similar for both modes 46,47 except for certain regions, 36,48 the biopsy targets initially identified on the MR image need to be readjusted to account for this morphological change in prostate.…”
Section: F I G U R Ementioning
confidence: 99%